Acute massive cerebellar infarction associated with craniocervical junction complex malformation: a case report and literature review. (3rd September 2018) - Wang, Wen-Tao; Liu, Ji-Jun; Duan, Kun; Bie, Xiaohua; Liu, Tuan-Jiang; Hao, Ding-Jun
Abstract: We report a case of acute massive cerebellar infarction associated with craniocervical junction (CVJ) complex malformation in a 21-year-old male. Timely surgical intervention prevented the deterioration of his neurological status.